EVALUATING THE EFFICIENCY OF URBAN PUBLIC TRANSPORT - CHERNII, VLADYSLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the main approaches to defining the essence of the concept of "efficiency", which made it possible to formulate the author’s vision of the content of this category. Public transport is an important component of public life, development of the country’s economy and environmental safety of the population. The world pandemic of coronavirus demonstrated the importance and criticality of the system of public transport for each state, because exactly the restrictions of movement and filling of public transport became an insuperable problem both for citizens and for those components of business and functioning of the country. Under such conditions, the issue of public transport efficiency is particularly acute, because the transport needs of the population must be met not only under uncertainty, but also in the perspective of sustainable development and in line with market and infrastructural circumstances. That is why the research of peculiarities of estimation of efficiency of urban public transport functioning acquires a special topicality. The author has characterised the peculiarities of content and components of efficiency of public transport. The own methodology of effectiveness assessment of public transport operation is presented and the specific set of initial data of such assessment is formulated. As a result, it was possible to approbate the author’s method on the data of the system of public transport in. Kiev. Using of methodology and carrying out of evaluation allowed the author to formulate the main substantiated ways of effectiveness increase of public transport and strategic vectors of further development. Analysis of quantitative characteristics of the system of public transport as an economic entity has determined that the main way of increasing its efficiency is increasing the profitability of transportation and number of passengers. As a result of analysis of the quality of public transport services, it is determined that the main directions of increasing their efficiency should be increasing the number of trips and introduction of a more convenient schedule. These are to be the main components of the strategy for further development of public transport in Kiev.